The Effect of Internet Banking on the Financial Performance of Nepalese Commercial Banks - Pandey, Preety (Nepalese Journal of Finance, 2025)
This study examines the effect of internet banking and financial performance of Nepalese commercial banks. Financial performance is selected as the dependent variable. Similarly, mobile banking, internet banking, agency banking, QR code, point of sale are selected as independent variables. This study is based on primary data with 124 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing the effect on financial performance of Nepalese commercial banks. The study showed that internet banking has a positive impact on financial performance. It means that higher the quality of internet banking higher will be the financial performance. Similarly, mobile banking has a positive impact on financial performance. It indicates that an increase in effective use of mobile banking leads to an increase in financial performance. Moreover, agency banking has a positive impact on financial performance. It indicates that an increase in agency banking leads to an increase in financial performance. Likewise, QR code has a positive impact on financial performance. It shows that the higher the use of QR code, the higher will be the financial performance. Similarly, point of sale has a positive impact on financial performance. It indicates that the higher the used of in point of sale higher will be the financial performance.